Asupan Zat Besi, Protein dan Vitamin C Sebagai Faktor Resiko Terjadinya Anemia pada Siswi di MTS Al- Amin Martapura Kabupaten Banjar Tahun 2013 - Yuliana Salman; Rosihan Anwar; Mijdefi Pauzi; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Iron-deficiency anemia is a common nutritional problem in the world. The prevalence of anemia in Indonesia is still quite high, which is 26,50% on female teenagers. Lot of female teenagers suffer from anemia, because adolescence is a period of growth which requires high nutrients including iron, protein also plays an important role in iron transportation inside the body, as well as increased consumption of vitamin C as much as 25-250 mg may increase the absorption of an iron 2-5 times. Based on the results of hemoglobin concentration (Hb) in MTs Al-Amin schoolgirl Martapura there are 90 students that 48,89% or 44 girls who suffer from anemia. This study aims to know intake of iron, protein and vitamin C as a risk factor for anemia in MTs Al-Amin schoolgirl Martapura Banjar District in 2013. This research using case control observations design. Samples as much as 88 students, 44 female students suffering from anemia (cases) and 44. variables using chi-square shows, iron intake obtained p = 0,01 and protein intake obtained values p = 0,00 which means that there is a relationship of iron and protein intake with the occurrence of anemia. At the same case the intake of vitamin C obtained p value = 0,13 which means that there is no relationship of vitamin C intake with anemia.